TANGGUNG JAWAB HUKUM PENGUSAHA KAPAL TERHADAP PENGGUNA JASA KAPAL JIKA TERJADI KECELAKAAN AKIBAT TIDAK LAYAKNYA KAPAL OPERASIONAL - Muhammad Riyan Adi Saputra (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
AbstractIn the development of the world, with the formation of a state is necessary law for the security of its citizens. The law regulates the entire device of the people's devices in the country. There are written laws, such as the 1945 Constitution, the Criminal Code Law, jurisprudence, treaties and so forth, made by the Executive Body together with representatives in the DPR, and there are also unwritten laws such as: customary law, law customs, etc., made by people empowered by the people, such as community leaders and recognized by the people and upheld by law enforcement.The entrepreneurs providing sea transport services, in this case play an important role to promote domestic trade because it helps facilitate the flow of freight in the form of goods and passengers (people) from one area to another. To manage it is not only required to operate the ship as a tool to provide sea freight services, it is also necessary knowledge of domestic trade, organization, administration, sound management, engineering, nautics, marine law, etc. and knowledge of the stockpiling procedures or compaction of the cargo in the space of each hatch of the ship in such a way that the maximum capacity of the vessel (full) and the capacity or carrying capacity of the vessel (down) or in other words is achieved full and down.